Mussel‐Inspired Polymer Carpets: Direct Photografting of Polymer Brushes on Polydopamine Nanosheets for Controlled Cell Adhesion. Issue 7 (15th December 2015) - Hafner, Daniel; Ziegler, Lisa; Ichwan, Muhammad; Zhang, Tao; Schneider, Maximilian; Schiffmann, Michael; Thomas, Claudia; Hinrichs, Karsten; Jordan, Rainer; Amin, Ihsan
Abstract : 2D mussel‐inspired polydopamine (PDA) nanosheets are prepared and exploited as a functional surface for grafting various polymer brushes. The PDA nanosheet and its polymer‐brush derivatives show lateral integrity and are robust; therefore, they can be detached from their substrates. Cell‐adhesion tests show that the PDA nanosheet promotes cell growth and attachment, while a PDA‐based poly(3‐sulfopropyl methacrylate) carpet exhibits nonfouling behavior.